2020
DOI: 10.15252/emmm.202012724
|View full text |Cite
|
Sign up to set email alerts
|

A novel P2X2‐dependent purinergic mechanism of enteric gliosis in intestinal inflammation

Abstract: Enteric glial cells (EGC) modulate motility, maintain gut homeostasis, and contribute to neuroinflammation in intestinal diseases and motility disorders. Damage induces a reactive glial phenotype known as "gliosis", but the molecular identity of the inducing mechanism and triggers of "enteric gliosis" are poorly understood. We tested the hypothesis that surgical trauma during intestinal surgery triggers ATP release that drives enteric gliosis and inflammation leading to impaired motility in postoperative ileus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 77 publications
1
67
1
Order By: Relevance
“…As infiltrating leukocytes numbers declined, we anticipate that proinflammatory cytokine induction derives from resident-producing cells rather than from the infiltrating cells. For IL-1β and IL6, this could be enteric glia that is known to contribute to POI development [16,17]. Unfortunately, we were unable to measure discrete gene expression profiles from resident MMs isolated in the late phase of POI as MMs can be hardly separated from infiltrating monocyte-derived macrophages due to an overlapping marker expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As infiltrating leukocytes numbers declined, we anticipate that proinflammatory cytokine induction derives from resident-producing cells rather than from the infiltrating cells. For IL-1β and IL6, this could be enteric glia that is known to contribute to POI development [16,17]. Unfortunately, we were unable to measure discrete gene expression profiles from resident MMs isolated in the late phase of POI as MMs can be hardly separated from infiltrating monocyte-derived macrophages due to an overlapping marker expression.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical handling of the bowel has been shown to activate MMs, which in turn trigger and maintain an acute inflammation leading to postoperative ileus (POI) [11], a transient motility disorder of the muscularis externa [12,13]. In the early phase of POI, MMs [11,14,15] and enteric glia cells [16,17] are activated and mediate the release of proinflammatory cytokines. The late phase is characterized by extravasation of blood-derived leukocytes, more precisely characterized as CD45 + Ly6C + Ly6Gmonocytes and CD45 + Ly6C + Ly6G + neutrophils [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…They modulate neural activity in the enteric nervous system and can be activated by mechanical forces that initiate a neuro-inflammatory process [20]. Preclinical research of our group demonstrated an IL-1 receptor-type 1 (IL1R1) and P2X2-dependend effect on POI [19]. Figure 1 provides a current understanding of the neuroimmune interactions in gastrointestinal dysmotility.…”
Section: Pathophysiology Of Poimentioning
confidence: 96%
“…Further, animal studies revealed that a network of resident macrophages plays a central role in orchestrating this inflammation [15,16] involving numerous cytokines but also prostaglandins by inducing the expression of cyclooxygenase-2 (COX-2) as well as NO [17]. Moreover, the release of proinflammatory cytokines and chemokines by the enteric nervous system add to that effect [18,19]. Recently, research focused on the population of enteric glial cells.…”
Section: Pathophysiology Of Poimentioning
confidence: 99%
“…Primary enteric glia cell cultures were obtained by sacrificing C57BL/6 mice 8-16 weeks of age, extracting the small intestine as described previously [38]. After cleansing it with 20 mL of oxygenated Krebs-Henseleit buffer (126 mM NaCl; 2.5 mM KCl: 25 mM NaHCO3; 1.2 mM NaH2PO4; 1.2 mM MgCl2; 2.5 mM CaCl2, 100 IU/mL Pen, 100 IU/mL Strep and 2.5μg/mL Amphotericin), the small bowel was cut in 3-5 cm long segments and kept in oxygenated ice-cold Krebs-Henseleit buffer.…”
Section: Generation and Cultivation Of Primary Egcmentioning
confidence: 99%